3(2x-3)=(3x+8)

Simple and best practice solution for 3(2x-3)=(3x+8) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(2x-3)=(3x+8) equation:



3(2x-3)=(3x+8)
We move all terms to the left:
3(2x-3)-((3x+8))=0
We multiply parentheses
6x-((3x+8))-9=0
We calculate terms in parentheses: -((3x+8)), so:
(3x+8)
We get rid of parentheses
3x+8
Back to the equation:
-(3x+8)
We get rid of parentheses
6x-3x-8-9=0
We add all the numbers together, and all the variables
3x-17=0
We move all terms containing x to the left, all other terms to the right
3x=17
x=17/3
x=5+2/3

See similar equations:

| X-3/3=2x+1/7 | | (4x+5)÷2x=39÷12 | | x+8+15=-4 | | 6x-x=4-4 | | a-30=3 | | (x–2)(x–5)=18 | | 3.8x–7=8.2 | | ?-6x5=10 | | x+(x*0.20)=1920 | | (9/7x)(14/3)(18x/6)=3 | | y2-15y-16=0 | | (x+(x*0.20))-1043=1920 | | x+(x*0.20)-1043=1920 | | 0.062=6.2×10n | | 3x-6(3-4x)=9x2 | | -3(-3x-3)+3=66 | | 5x^2-51x+5=0 | | -66=3(5b-2) | | 5x+x+23=3x+34 | | 4,8/15,36=x/8 | | -z+1=1-z | | 64x^​2+64x+16=0 | | 64x​2​​+64x+16=0 | | x=0.02x^2+0.05x+0.04 | | 18=3y= | | 81z^2-4=0 | | 18-(3a-12)=8a | | -2(-2y+2)=16 | | -2(-2y=2)=16 | | 4x+33=-8x+9+5x | | 3a+7=12+4a | | 27x^2-72x-27=0 |

Equations solver categories